2020
DOI: 10.1002/14651858.cd013165.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Potassium binders for chronic hyperkalaemia in people with chronic kidney disease

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:To assess the benefits and harms of potassium binders for treating chronic hyperkalaemia among adults and children with CKD.1 Potassium binders for chronic hyperkalaemia in people with chronic kidney disease (Protocol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 87 publications
0
22
0
1
Order By: Relevance
“…Patiromer and SZC are generally well-tolerated. Overall, Patiromer related adverse events occurred in ∼20% of the patients enrolled the major trials (54). These events include electrolyte disorders, such as hypomagnesemia and hypokalemia, and mild gastrointestinal symptoms, such as constipation (8%), diarrhea (5%), nausea and flatulence (65).…”
Section: Safety and Tolerability Of News Potassium Bindersmentioning
confidence: 99%
“…Patiromer and SZC are generally well-tolerated. Overall, Patiromer related adverse events occurred in ∼20% of the patients enrolled the major trials (54). These events include electrolyte disorders, such as hypomagnesemia and hypokalemia, and mild gastrointestinal symptoms, such as constipation (8%), diarrhea (5%), nausea and flatulence (65).…”
Section: Safety and Tolerability Of News Potassium Bindersmentioning
confidence: 99%
“…Although several systematic reviews have examined the efficacy of these new compounds in lowering serum potassium [ 14 , 15 , 16 , 17 ], no SRs have analyzed whether NPBs allow the optimization of RAASi therapy in HF patients. This is the first quick review in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized trials have recently demonstrated efficacy and tolerability of new K-binders agents leading to remarkably lower rates of RAASI discontinuation as compared to traditional anti-hyperkalemic therapy [ 46 , 47 ]. These data call for real-world studies conducted in renal clinics, on large number of patients and with long follow up, to verify effectiveness on hard outcomes [ 48 ].…”
Section: Discussionmentioning
confidence: 99%